Inhibition of protein kinase C beta phosphorylation activates nuclear factor-kappa B and improves postischemic recovery in type 1 diabetes - Alleboina, Satyanarayana (Exp Biol Med (Maywood), 2020)
Peripheral artery disease (PAD) is a major health problem and is caused by atherosclerosis in arteries outside the heart leading to impaired blood flow. The presence of diabetes significantly increases the likelihood of having worse outcomes in PAD, and the molecular mechanisms involved are poorly understood. Hyperglycemia in diabetes activates the nuclear factor-kappa B (NF-κB) pathway, and chronic inflammation in diabetes is associated with vascular complications. Ischemia also activates NF-κB signaling that is important for perfusion recovery in experimental PAD. We hypothesized that prolonged exposure of endothelial cells to high glucose in diabetes impairs ischemic activation of the NF-κB pathway and contributes to poor perfusion recovery in experimental PAD. We assessed the effect of high glucose and ischemia on canonical and non-canonical NF-κB activation in endothelial cells and found both conditions activate both pathways. However, exposure of endothelial cells to high glucose impairs ischemia-induced activation of the canonical NF-κB pathway but not the non-canonical pathway. We probed an array of antibodies against signaling proteins in the NF-κB pathway to identify proteins whose phosphorylation status are altered in endothelial cells exposed to high glucose. Protein kinase C beta (PKCβ) was among the proteins identified, and its role in impaired ischemia-induced activation of NF-κB during hyperglycemia has not been previously described. Inhibition of PKCβ improves ischemia-induced NF-κB activation in vitroand in vivo. It also improves perfusion recovery in diabetic mice following experimental PAD. Thus, in diabetes, PKCβ phosphorylation contributes to impaired ischemic activation of NF-κB and likely a mechanism contributing to poor PAD outcomes. IMPACT STATEMENT: Diabetes worsens the outcomes of peripheral arterial disease (PAD) likely in part through inducing chronic inflammation. However, in PAD, recovery requires the nuclear factor-kappa B (NF-κB) activation, a known contributor to inflammation. Our study shows that individually, both ischemia and high glucose activate the canonical and non-canonical arms of the NF-κB pathways. We show for the first time that prolonged high glucose specifically impairs ischemia-induced activation of the canonical NF-κB pathway through activation of protein kinase C beta (PKCβ). Accordingly, inhibition of PKCβ restores the ischemia-induced NF-κB activity both in vitroin endothelial cells and in vivoin hind limbs of type 1 diabetic mice and improves perfusion recovery after experimental PAD. Thus, this study provides a mechanistic insight into how diabetes contributes to poor outcomes in PAD and a potential translational approach to improve PAD outcomes.